REMEDIASI RESIDU INSEKTISIDA KLORPIRIFOS PADA PERTANAMAN CABAI MERAH (Capsicum annum L.) DI TANAH TEKSTUR RINGAN DAN TEKSTUR BERAT - Poniman, Poniman; Ardiwinata, A. N.; Muanisah, U.; Wahyuni, Sri (JURNAL LITBANG PROVINSI JAWA TENGAH, 2021)
Chlorpyrifos is widely used by farmers as a contact poison to control leaf and fruit pests in red chilies. Chlorpyrifos is very toxic to the environment and to living things, although it is easily degraded and has a short half-life. Remediation materials in the form of activated charcoal, biochar, and microbial consortium are effective remediation technologies to reduce insecticide residues. Each compound has different characteristics based on the type and texture of the soil. This research aims to obtain the ability of remediation technology for Chlorpyrifos insecticide residues in red chili on light and heavy textured soils. The research was carried out in the screen house of the Indonesian Agricultural Environment Research Institute (IAERI) between May to November 2017. The results showed that the two soil textures had different characteristics of Chlorpyrifos residue remediation technology. The best technology to reduce Chlorpyrifos residue in light-textured soils is the 2 L/ha consortium microbial treatment, while for heavy-textured soils is biochar-coated urea.